One-year safety and tolerability of tezepelumab in Japanese patients with severe uncontrolled asthma: results of the NOZOMI study. (4th March 2023) - Shinkai, Masaharu; Ebisawa, Motohiro; Fukushima, Yasushi; Takeuchi, Satomi; Okada, Hiroshi; Tokiyo, Tatsuro; Hayashi, Nobuya; Takikawa, Mami; Colice, Gene; Almqvist, Gun
Abstract: Objective: To assess the long-term safety of tezepelumab in Japanese patients with severe uncontrolled asthma. Methods: This phase III, 52-week, open-label, single-arm study (NOZOMI, NCT04048343) evaluated the safety/tolerability of subcutaneous (SC) tezepelumab 210 mg every 4 weeks (Q4W) in Japanese patients aged 12–80 years with severe uncontrolled asthma using medium- to high-dose inhaled corticosteroids and at least one additional asthma controller medication, with/without oral corticosteroids. Exploratory outcomes included efficacy (asthma exacerbations, lung function, and asthma control), pharmacokinetic parameters, and immunogenicity. Results: Among 65 patients (median age 52 years), 39 (60%) experienced 94 adverse events (AEs; predominantly nasopharyngitis [13/65]) of mild (49.2%), moderate (7.7%), or severe (3.1%) intensity. Two patients had transient injection site erythema related to tezepelumab. Four patients reported serious AEs unrelated to tezepelumab and one AE led to treatment discontinuation. AEs of special interest were infrequent and generally mild/moderate. Apart from a decrease in blood eosinophils (an expected pharmacodynamic effect), no notable trends/clinically relevant changes in hematology, clinical chemistry, or urinalysis parameters were observed. Among exploratory outcomes, tezepelumab was associated with a low annualized asthma exacerbation rate over the study period (0.11/patient-year), improved lung function (mean [standard deviation] change from baseline of 0.075 [0.226] L in pre-dose/pre-bronchodilator forced expiratory volume in 1 s), and better asthma control versus baseline (responder rate: 71.4% at Week 52). Conclusion: Tezepelumab 210 mg SC Q4W in Japanese patients with severe uncontrolled asthma showed safety/tolerability profiles similar to international data, with low exacerbation rates and improvements in lung function and asthma control.